Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.24017/science.2019.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge Regarding FoodDrug Interaction in the Intensive Care and Emergency Hospitals

Abstract: Usually supplement is essential and fundamental components for ensure and creating the human body, also drugs seem to survey the life of each individual and ensure the wellbeing for a long life aimed most of illness, but in case nourishment sedate interaction ignored since of information shortage almost it or any reason maybe lead to futile of medicine for the patients or cause life threatening condition because of that, one of the most significant ethical point in every health care setting in the world is pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This result may be due to nearly two thirds of studied nurses had technical institute of nursing, lack of refreshment of knowledge, continuous training program and insufficient courses related to toxicological emergencies . This finding is supported by (Lafi, Kamali & Sharif, 2019) nurses working in emergency department had adequate practices in management sever cases and due to recurrent and multiple cases of poisoning and nearly half of nurses have adequate experience in emergency unit and poisoning center carefully to saving patients life. This finding goes in the same line with the study done by (Mohamed, 2020) which showed that more than half of the nurses had competent practice regarding care of patients with acute organophosphate poisoning.…”
Section: Discussionmentioning
confidence: 80%
“…This result may be due to nearly two thirds of studied nurses had technical institute of nursing, lack of refreshment of knowledge, continuous training program and insufficient courses related to toxicological emergencies . This finding is supported by (Lafi, Kamali & Sharif, 2019) nurses working in emergency department had adequate practices in management sever cases and due to recurrent and multiple cases of poisoning and nearly half of nurses have adequate experience in emergency unit and poisoning center carefully to saving patients life. This finding goes in the same line with the study done by (Mohamed, 2020) which showed that more than half of the nurses had competent practice regarding care of patients with acute organophosphate poisoning.…”
Section: Discussionmentioning
confidence: 80%